2021
DOI: 10.3390/diagnostics11030509
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic Lateral Sclerosis and Frontotemporal Lobar Degenerations: Similarities in Genetic Background

Abstract: Amyotrophic lateral sclerosis (ALS) is a devastating, uniformly lethal progressive degenerative disorder of motor neurons that overlaps with frontotemporal lobar degeneration (FTLD) clinically, morphologically, and genetically. Although many distinct mutations in various genes are known to cause amyotrophic lateral sclerosis, it remains poorly understood how they selectively impact motor neuron biology and whether they converge on common pathways to cause neuronal degeneration. Many of the gene mutations are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 221 publications
(161 reference statements)
0
9
0
Order By: Relevance
“…The discovery of genetic aetiology in ≈70% of familial and ≈10% of non-hereditary ALS cases pointed out possible causes of motor neurons degeneration. However, ALS cases linked to genetic mutations are less than 10-15% and these mutations affect more than 30 genes encoding for proteins that have disparate functions 1,2 . In fact, some of these proteins act by binding DNA and/or RNA [TAR DNA binding protein-43 (TDP-43), fused in sarcoma/translocated in liposarcoma (FUS), matrin-3 [3][4][5] ]; some are enzymes [Cu/Zn superoxide dismutase 1 (SOD1), and valosin-containing protein (VCP) 6,7 ]; others are implicated in protein degradation (p62/sequestosome-1) 8 , contribute to the formation of cytoskeleton (profilin-1) 9 or regulate intracellular trafficking pathways [chromosome 9 open reading frame 72 (C9orf72)] 10 .…”
mentioning
confidence: 99%
“…The discovery of genetic aetiology in ≈70% of familial and ≈10% of non-hereditary ALS cases pointed out possible causes of motor neurons degeneration. However, ALS cases linked to genetic mutations are less than 10-15% and these mutations affect more than 30 genes encoding for proteins that have disparate functions 1,2 . In fact, some of these proteins act by binding DNA and/or RNA [TAR DNA binding protein-43 (TDP-43), fused in sarcoma/translocated in liposarcoma (FUS), matrin-3 [3][4][5] ]; some are enzymes [Cu/Zn superoxide dismutase 1 (SOD1), and valosin-containing protein (VCP) 6,7 ]; others are implicated in protein degradation (p62/sequestosome-1) 8 , contribute to the formation of cytoskeleton (profilin-1) 9 or regulate intracellular trafficking pathways [chromosome 9 open reading frame 72 (C9orf72)] 10 .…”
mentioning
confidence: 99%
“…3.1.1. Genetic and Pathological Overlap between ALS and FTD ALS has a close association with frontotemporal dementia (FTD), sharing a common molecular etiology with this condition [36]. Roughly 15% of individuals diagnosed with FTD develop motor neuron disease (MND), while conversely, up to 50% of those with MND exhibit clear signs of cognitive defects [37].…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…The First Insight into the Hereditary Fusion Gene Landscape of ASL Supplemental Materials NYGC ALS Consortium Hemali Phatnani 5 , Justin Kwan 6 , Dhruv Sareen 7,8 , James R. Broach9, Zachary Simmons 10 , Ximena Arcila-Londono 11 , Edward B. Lee 12 , Vivianna M. Van Deerlin 12 , Neil A. Shneider 13 , Ernest Fraenkel 1 , Lyle W. Ostrow 14 , Frank Baas 15,16 , Noah Zaitlen 17 , James D. Berry 18,19 , Andrea Malaspina 19,20,21 , Pietro Fratta 22 , Gregory A. Cox 23 , Leslie M. Thompson 24,25 Johns Hopkins School of Medicine, Baltimore, MD, USA. 15 Department of Neurogenetics, Academic Medical Centre, Amsterdam, The Netherlands.…”
Section: Acknowledgesmentioning
confidence: 99%
“…Many studies have shown clinical, pathological, and genetic commonalities between them. Therefore, ASL and FTD have now considered two manifestations of one disease continuum of the FTD-ALS spectrums 5 .…”
Section: Introductionmentioning
confidence: 99%